The domestic fruit supply: Evolutions and trends - Viorica Gavrilă (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
Domestic fruit supply stability is evaluated taking into consideration the dynamic interactions between production and consumption and testing the synchronization of the supply flow with the consumption demand. The statistical data series from the period 2002-2014 were used, and the forecast of fruit consumption, of the areas under orchards and of average yields was made through the exponential levelling method. The estimates indicate an increase of fruit consumption, except for apples, a decrease of areas and a slight increase of average yields. It can be noticed that under the background of decreasing areas, the slight increase of yields represents only an attenuation factor of foreseeable deficit.
Keywords: Q11; 330; fruit; supply; demand